2009
DOI: 10.1108/00070700911001040
|View full text |Cite
|
Sign up to set email alerts
|

The influence of consumer involvement on quality signals perception

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
44
0
6

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(55 citation statements)
references
References 123 publications
(143 reference statements)
5
44
0
6
Order By: Relevance
“…Service quality can affect the customer's satisfaction directly and positively but it has a negative relationship with the perceived risk (Bicen, 2015;Chen & Chang, 2005;Espejel et al, 2009). Researchers found that perceived risk can be controlled and reduced to avoid its harmful effects.…”
Section: Service Qualitymentioning
confidence: 99%
“…Service quality can affect the customer's satisfaction directly and positively but it has a negative relationship with the perceived risk (Bicen, 2015;Chen & Chang, 2005;Espejel et al, 2009). Researchers found that perceived risk can be controlled and reduced to avoid its harmful effects.…”
Section: Service Qualitymentioning
confidence: 99%
“…Consumer involvement has also been classified into enduring involvement and situation involvement by some other authors [55,[68][69][70][71]. Enduring involvement is referred to as the relevance of a product category that a consumer has with [72]. Situational involvement, as the name implies, is referred to consumers' involvement which is context specific and accordingly short-term in nature [72].…”
Section: Construct Reference Key Argumentmentioning
confidence: 99%
“…Enduring involvement is referred to as the relevance of a product category that a consumer has with [72]. Situational involvement, as the name implies, is referred to consumers' involvement which is context specific and accordingly short-term in nature [72].…”
Section: Construct Reference Key Argumentmentioning
confidence: 99%
See 1 more Smart Citation
“…The concept of brand involvement proposed by Espejel, Fandos and Flavián [11], and the concept of brand value, proposed by Šerić, Gil-Saura and Mikulić [12] to develop an integrated model (see Fig. 1).…”
Section: Brand Valuementioning
confidence: 99%